Gender differences in research areas, methods and topics: Can people and thing orientations explain the results?. Issue 1 (February 2019) - Thelwall, Mike; Bailey, Carol; Tobin, Catherine; Bradshaw, Noel-Ann
Highlights: This article reports the share of male and female first authored articles in the USA in 285 narrow and 26 broad fields in 2017. Gender differences in research fields and topics cannot be fully explained by people/thing interest dimensions from psychology. There is greater female interest in veterinary science and cell biology and greater male interest in abstraction, patients, and power/control fields. Females researches seem more likely to use exploratory and qualitative methods rather than quantitative methods. Abstract: Although the gender gap in academia has narrowed, females are underrepresented within some fields in the USA. Prior research suggests that the imbalances between science, technology, engineering and mathematics fields may be partly due to greater male interest in things and greater female interest in people, or to off-putting masculine cultures in some disciplines. To seek more detailed insights across all subjects, this article compares practising US male and female researchers between and within 285 narrow Scopus fields inside 26 broad fields from their first-authored articles published in 2017. The comparison is based on publishing fields and the words used in article titles, abstracts, and keywords. The results cannot be fully explained by the people/thing dimensions. Exceptions include greater female interest in veterinary science and cell biology and greater male interest in abstraction, patients, and power/control fields, such as politics and law. These may be due to other factors, such as the ability of a career to provide status or social impact or the availability of alternative careers. As a possible side effect of the partial people/thing relationship, females are more likely to use exploratory and qualitative methods and males are more likely to use quantitative methods. The results suggest that the necessary steps of eliminating explicit and implicit gender bias in academia are insufficient and might be complemented by measures to make fields more attractive to minority genders.